Population Synthesis of Black Hole X-Ray Binaries - Shao, Yong; Li, Xiang-Dong (The Astrophysical journal, 2020)
We present a systematic study of the X-ray binaries (XRBs) containing a black hole (BH) and a nondegenerate companion, in which mass transfer takes place via either capturing the companion's wind or Roche lobe overflow (RLO). As shown in our previous work, which focused on the formation and evolution of detached BH binaries, our assumed models relevant to BHs' progenitors predicted significantly different binary properties. In this paper, we further follow the evolutionary paths of BH systems that appear as XRBs. By use of both binary population synthesis and detailed binary evolution calculations, we can obtain the potential population of BH XRBs. Distributions at the current epoch of various binary parameters have been computed. The observed sample of wind-fed XRBs can be well reproduced under the assumptions of all of our models. Wind-fed XRBs are expected to be so rare ( 100) that only a couple such systems have been detected. Comparison of known RLO XRBs with the calculated distributions of various binary parameters indicates that only the models assuming relatively small masses for BH progenitors can roughly match the observations. Accordingly we estimate that there are hundreds of RLO XRBs in the Milky Way, of which the majority are low-mass XRBs. RLO systems may become ultraluminous X-ray sources (ULXs) if the BH accretes at a very high rate, and we expect that about a dozen ULXs with a BH accretor may exist in a Milky Way-like galaxy.